A SCIENTIFIC APPROACH TO PRASAVA PRAKRIYA (LABOUR) AN AYURVEDIC VIEW - Pal, *Meenakshi; Sharma, Sushila; Pushpalatha, B.; Bharathi, K. (International Journal of Ayurveda and Pharma Research, 2015)
Pregnancy is the most important event in the life of every woman. Passage throw the birth canal is the most hazardous journey made by an individual in his or her life, the amount of pain and discomfort a woman has to face is far more than any pain imaginable. The normal labour can turn to pathological at any time and rightly described that at the time of child birth, womens one leg lies in this Loka and other in Yamaloka. It is necessary to know the causes of initiation of labour, duration of labour, the various stages of labour and the proper mechanism to carry out process of labour normally in order to prevent life threatening complications to the mother as well as to the foetus. An elaborate description of Prasava is given in Ayurvedic samhitas which help us tremendously to understand concept of Prakrit prasava (normal labour). People are not aware of concept of labour in Ayurveda though it is a very scientifically described in Ayurvedic texts. In the present article an attempt is made to throw light on the scientific outlook of management of labour described in Ayurveda.